Avaliação morfofisiológica de duas variedades tradicionais de arroz da região pantaneira mato-grossense, submetidas a distintos níveis de fertilização - Espinoza, Diana Medina (2017)
In Brazil, the germoplasm bank of several agronomic species is limited. This make the identification of new non-commercial genetic materials always greatly accepted. These varieties usually are produced in isolated communities and maintained by cultural heritage. The Community of São Pedro de Joselândia, Barão de Melgaço, Mato Grosso, have maintained and protected several autochthonous materials. Part of these materials consist of two traditional varieties of rice that showed medium protein content in previous studies, making them interesting from the food security point of view. Considering the information above, the objective was to evaluate the growth, physiological performance and efficiency in nutrient use in these traditional rice varieties, grown under different nutritional levels. There was establish a factorial design experiment having two factors, the varieties and four levels of fertilization. The traditional varieties used were Branquinho and Agulhinha Vermelho. The levels of fertilizations were no fertilization, low fertilization (100 kg ha-1 de N, 120 kg ha-1 de P2O5 e 80 kg ha-1 de K2O), medium fertilization (two times the low fertilization dose), and high fertilization (three times the low fertilization dose). Both traditional varieties were responsive to fertilization, increasing biomass production, growth, photosynthetic performance and nutrient uptake. There was a 23% increase un leaf production, up to 20 times more tillers per plant and up to 75% increase in leaf area, when plants were grown under low fertilization, without showing differences between the higher levels. Yield and nutrient use efficiency were compromised due to the attack of plagues and diseases, which limited mainly the grain filling. Increases in the dose of fertilization resulted in reduction on the nutrient use efficiency. The main effect of the fertilization was in the growth of the plants, which was the limiting factor in the reaming characteristics evaluated, being nitrogen the more responsible for these results.